2018
DOI: 10.1002/ajmg.a.38700
|View full text |Cite
|
Sign up to set email alerts
|

Novel de novo pathogenic variant in the NR2F2 gene in a boy with congenital heart defect and dysmorphic features

Abstract: The NR2F2 gene plays an important role in angiogenesis and heart development. Moreover, this gene is involved in organogenesis in many other organs in mouse models. Variants in this gene have been reported in a number of patients with nonsyndromic atrioventricular septal defect, and in one patient with congenital heart defect and dysmorphic features. Here we report an 11-month-old Caucasian male with global developmental delay, dysmorphic features, coarctation of the aorta, and ventricular septal defect. He wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Mapping a 5.8 Mb deletion in a patient with CHD, Nakamura et al [117] identified COUP-TFII as a putative candidate gene. Association of COUP-TFII to CHD was later confirmed by other groups [118][119][120][121][122]. Interestingly, deletion of 15q is not the only possible mutation happening in CHD in the COUP-TFII locus but single point missense mutations of the NR are sufficient to induce the pathogenic phenotype [120,122].…”
Section: Cardiovascular Diseasesmentioning
confidence: 80%
“…Mapping a 5.8 Mb deletion in a patient with CHD, Nakamura et al [117] identified COUP-TFII as a putative candidate gene. Association of COUP-TFII to CHD was later confirmed by other groups [118][119][120][121][122]. Interestingly, deletion of 15q is not the only possible mutation happening in CHD in the COUP-TFII locus but single point missense mutations of the NR are sufficient to induce the pathogenic phenotype [120,122].…”
Section: Cardiovascular Diseasesmentioning
confidence: 80%
“…Furthermore, the expression and functional profile of NR2F2 overlap at least partially with those of the well-established BAV-associated genes GATA4, GATA5 and NKX2-5 during embryonic cardiogenesis (27)(28)(29). Pathogenic mutations in NR2F2, GATA4-6 and NKX2-5 have been reported to cause similar cardiovascular developmental anomalies in animals and humans, including defects in the cardiac outflow tract, septum and endocardial cushion (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). These findings suggest NR2F2 as a preferred candidate gene of human BAV and provide a theoretical basis for screening of the gene.…”
Section: Nr2f2 Loss-of-function Mutation Is Responsible For Congenital Bicuspid Aortic Valvementioning
confidence: 97%
“…NR2F1 and NR2F2 are both expressed in human atrial cardiomyocytes [128]. However, to this point, only mutations in NR2F2 in humans have been associated with CHDs [1,2,119,120,129,130] (Table 1). NR2F1 and NF2F2 are required for the differentiation of atrial cardiomyocytes in human embryonic stem cells (hESCs) [128].…”
Section: Zebrafish As a Model For Human Atrial And San Defectsmentioning
confidence: 99%
“…However, nr2f1a mutants also have an expanded AVC [70], which we posit could lead to AVSDs from improper alignment and valve specification. Interestingly, although Nr2fs have historically been associated with atrial development, human NR2F2 mutations are also associated with CHDs affecting the ventricle, including VSDs, left ventricular outflow tract obstruction (LVOTO), and double outlet right ventricle (DORV) [1,2,119,120]. Additionally, mutations in NR2F1 and NR2F2 have been associated with craniofacial defects in humans [120,130].…”
Section: Zebrafish As a Model For Human Atrial And San Defectsmentioning
confidence: 99%
See 1 more Smart Citation